2015
DOI: 10.18632/oncotarget.6515
|View full text |Cite
|
Sign up to set email alerts
|

MULTIMERIN2 binds VEGF-A primarily via the carbohydrate chains exerting an angiostatic function and impairing tumor growth

Abstract: Angiogenesis is a key process occurring under both physiological and pathological conditions and is a hallmark of cancer. We have recently demonstrated that the extracellular matrix (ECM) molecule MULTIMERIN2 exerts an angiostatic function through the binding to VEGF-A. In this study we identify the region of the molecule responsible for the binding and demonstrate that the interaction involves the carbohydrate chains. MULTIMERIN2 interacts with other VEGF-A isoforms and VEGF family members such as VEGF-B, -C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 63 publications
(47 reference statements)
0
41
0
Order By: Relevance
“…This depends on its ability to sequester VEGF-A and inhibit VEGFR-2 activation [224,225]. The binding capability has been pinpointed in a region towards the N-terminus of the molecule [225].…”
Section: The Eden Family: Two Members With Opposite Functionsmentioning
confidence: 99%
See 3 more Smart Citations
“…This depends on its ability to sequester VEGF-A and inhibit VEGFR-2 activation [224,225]. The binding capability has been pinpointed in a region towards the N-terminus of the molecule [225].…”
Section: The Eden Family: Two Members With Opposite Functionsmentioning
confidence: 99%
“…This depends on its ability to sequester VEGF-A and inhibit VEGFR-2 activation [224,225]. The binding capability has been pinpointed in a region towards the N-terminus of the molecule [225]. The VEGF-binding activity primarily occurs through the carbohydrate chains, since their removal significantly compromises, the binding [225].…”
Section: The Eden Family: Two Members With Opposite Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we found that CLEC14A is upregulated during the morphogenesis of endothelial progenitor cells into endothelial cells (ECs) (14). Recently, SILAC-based (stable isotope labeling with amino acids in cell culture-based) proteomics revealed that CLEC14A expression is enhanced in ECs during tubule morphogenesis and regulates cell-extracellular matrix adhesion to multimerin 2 (MMRN2), a suppressor of VEGF/VEGFR signaling during angiogenesis (15). Moreover, CLEC14A expression was significantly higher in the blood vessels of the tumor than in those of adjacent normal tissue (16), along with robust detection in tumor ECs and Controlled angiogenesis and lymphangiogenesis are essential for tissue development, function, and repair.…”
Section: Introductionmentioning
confidence: 99%